COGITO ERGO SUM : EXPLORATION OF RATIONALISM AND CERTAINTY IN THE CONSTRUCTION OF KNOWLEDGE - anggraini, Oci; Julita, Neli; Nafsih, Syarifatun (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
This research conducts an in-depth exploration of Rene Descartes famous statement "Cogito ergo sum", with a focus on aspects of rationalism and certainty in the construction of knowledge. The research question underlying this study is to what extent cogito ergo sum is the basis for understanding the relationship between rationalism and certainty, and how this concept shapes the paradigm of human knowledge this research to uncover the hidden philosophical meaning in the statement cogito ergo sum, identify its conceptual implications, and explore its impact on human understanding of knowledge. The research method used is a literature review with philosophical analysis, and text analysis to explore the philosophical meaning of Cogito ergo sum as well as related studies in philosophy and knowledge as well as presenting new insights into the relationship between rationalism and certainty in the view of Rene Descartes. The results of this research reveal the complexity of Rene Descartes' thinking regarding rationalism and certainty, highlighting that cogito ergo sum is an important foundation in our understanding of knowledge. and has a significant impact on shaping the paradigm of human knowledge, placing reason as the main instrument in achieving absolute truth.